The bend in RNA created by the trans-activation response element bulge of human immunodeficiency virus is straightened by arginine and by Tat-derived peptide. - Zacharias, M (1995)
The trans-activation response element (TAR) found near the 5' end of the viral RNA of the human immunodeficiency virus contains a 3-nt bulge that is recognized by the virally encoded trans-activator protein (Tat), an important mediator of transcriptional activation. Insertion of the TAR bulge into double-stranded RNA is known to result in reduced electrophoretic mobility, suggestive of a bulge-induced bend. Furthermore, NMR studies indicate that Arg causes a change in the structure of the TAR bulge, possibly reducing the bulge angle. However, neither of these effects has been quantified, nor have they been compared with the effects of the TAR-Tat interaction. Recently, an approach for the quantification of bulge-induced bends has been described in which hydrodynamic measurements, employing the method of transient electric birefringence, have yielded precise estimates for the angles of a series of RNA bulges, with the angles ranging from 7 degrees to 93 degrees. In the current study, transient electric birefringence measurements indicate that the TAR bulge introduces a bend of 50 degrees +/- 5 degrees in the absence of Mg2+. Addition of Arg leads to essentially complete straightening of the helix (to < 10 degrees) with a transition midpoint in the 1 mM range. This transition demonstrates specificity for the TAR bulge: no comparable transition was observed for U3 or A3 (control) bulges with differing flanking sequences. An essentially identical structural transition is observed for the Tat-derived peptide, although the transition midpoint for the latter is near 1 microM. Finally, low concentrations of Mg2+ alone reduce the bend angle by approximately 50%, consistent with the effects of Mg2+ on other pyrimidine bulges. This last observation is important in view of the fact that most previous structural/binding studies were performed in the absence of Mg2+.